Penerapan Model Pembelajaran Cooperative Integrated Reading and Composition (CIRC) dalam Meningkatkan Keterampilan Literasi Membaca dan Hasil Belajar Siswa - Trivonia Rani; Suhandi Astuti (Journal of Elementary School (JOES), 2023)
The purpose of this study was to find out how to improve Reading Literacy skills and student learning outcomes by using the Cooperative Integrated Reading and Composition (CRIC) Learning Model, as well as to find out the application of the Cooperative Integrated Reading and Composition (CRIC) Learning Model to improve reading literacy skills and learning outcomes class II students at SDN Kutowinangun 08 Salatiga. This type of research uses Classroom Action Research (PTK) while the type of data used in this research is Quantitative and Qualitative data. The results of the study show that in improving reading literacy skills and learning outcomes of second grade elementary school students by applying the Cooperative Integrated Reading and Composition (CRIC) learning model. This model requires students to improve reading literacy skills both from indicators of pronunciation, intonation, fluency, and clarity of voice when reading. This research can be said to be successful because the increase in reading skills in the action cycle I was 82.5 and in the action research cycle II it reached an average percentage of 87.87 and the learning outcomes of students reached 87.87 completeness from a predetermined performance indicator of 80. This study proves that the application of the Cooperative Integrated Reading and Composition (CRIC) learning model can improve reading literacy skills and learning outcomes of second grade elementary school students. Â Keywords: CIRC Learning Model, Reading Literacy Skills, Student Learning Outcomes